Transport Management System for Africa University: A Web-Based Solution for Fleet Operations - Moyo, Trust (Journal Dekstop Application (JDA), 2025)
Efficient transport management is essential for universities that coordinate vehicle fleets for academic and administrative purposes. At Africa University, reliance on manual systems caused delays, scheduling conflicts, and poor accountability. To address these issues, a web-based Transport Management System (TMS) was developed using ASP.NET, Visual Basic.NET, and SQL Server 2014. The system automates booking, approval, vehicle allocation, and reporting processes, providing secure access and real-time visibility for all users. Implementation of the TMS significantly improved efficiency by reducing processing time, minimizing paperwork, and enhancing coordination across departments. Automated workflows and audit trails strengthened accountability, while role-based access improved security and transparency. Users benefited from faster approvals, reliable scheduling, and accessible online services. For management, analytical dashboards enabled data-driven decisions on fleet utilization and resource optimization. Although challenges arose during implementation—such as system integration and user adaptation—ongoing training and technical support ensured successful adoption. The system’s modular structure supports future enhancements like GPS tracking, predictive maintenance, and mobile access. Overall, the TMS demonstrates how digital transformation can enhance institutional logistics, reduce operational costs, and promote sustainable management practices at Africa University.